Barriers to moral development of adolescents and parental responsibility: the case of Malay working parents - Abd Rashid, Adnan; Mamat , Arifin; Ibrahim, Mohd Burhan (Academicians' Research Center (ARC), 2014)
Over the last decade, parental education in Malaysia has been the focus of increased attention by the government and non-government organizations. Despite the numerous studies discussing parental roles and responsibilities for the emotional and physical development of adolescents, there remains a paucity of research concerning the impediments to the moral development of adolescents and the necessary parental practices to overcome such problems of morality. It is to this end that this study is aimed. For this purpose, the study examines the dimensions of awareness concerning the impediments to the moral development of adolescents among Malaysian parents, and the extent to which the ‘parental awareness-practice scale’ (PAP) is a reliable measure for this issue. The researcher lists the barriers impeding the moral development of adolescents as derived from a review of the relevant empirical literatures. Similarly, the practices and activities preferred by parents to overcome this challenge are also listed. The study developed two scales viz. PAIMD and PP, translated them into ‘Bahasa Malaysia’ and piloted the scale to improve reliability and validity to better suit the Malaysian context. The dimensions of parental awareness (α = .80) include awareness of improper parenting (α= .79), ideological problem (α = .64), internal characteristics (α = .84), and situational influences (α = .65), while dimensions of parental practices (α = .90) are mastering learning resources (α = .85), authoritative communication (α = .87), teaching morality (α = .70), and self-regulation (α = .80). The study identified and discussed the relationship of parental awareness of the barriers to adolescents’ morality and parental practices (r = .186, p = <0.01). In the data set, no systematic pattern and hierarchical trends were observed among the parents in terms of morality awareness and their parenting practices across gender, level of education, type of working organization, and location of residence. The findings have implications for raising parental awareness on protecting adolescents from the agents of moral decline. It is hoped that this study will contribute in its own unique way to fostering greater wellbeing in Malaysian society in line with tenth Malaysia plan 2011-2015.